(untitled) (Third Sector Social Economic Review, 2024)
Consumers’ perceptions, attitudes, and personality traits are among the key factors that influence their purchasing behavior and the evaluation of products produced by businesses. In this context, consumer psychology plays a decisive role in shaping the beliefs and attitudes that consumers develop toward brands. Businesses strengthen their marketing strategies by utilizing the placebo effect to steer consumers toward making purchases. The placebo effect emerges as a mechanism that triggers the purchasing tendency by increasing the perceived value of the products or services offered to consumers. This effect is particularly important in the planning phase of promotional activities, where businesses capitalize on its benefits. The purpose of this study is to examine the impact of promotion activities and the placebo effect on consumer purchasing behavior. Within the scope of the research, the placebo effect of promotion activities is analyzed from various perspectives, including the country of origin effect, the concept of scarcity, sales promotion activities, product packaging, digital marketing, and social media efforts. The data set for the study was collected from 429 participants through an online survey, and the hypotheses were analyzed using the SPSS 25.0 statistical program. Statistical methods such as scale averages, Ligid model analysis, and correlation tests were employed during data analysis. The results of the research revealed that the placebo effect has a significant impact on consumers’ purchase intentions. Furthermore, the study concluded that when promotional activities are effectively utilized, they can create positive changes in consumer perceptions and guide purchasing decisions. These findings highlight the importance of considering the placebo effect in the development of marketing strategies by businesses.